The Effectiveness of Massage Rolling (back) on Increasing Breast Production in Postpartum Mothers - Eka Maya Saputri; Juli Selvi Yanti (Institute Of Computer Science (IOCS), 2021)
This research is motivated by the lack of milk production and the production is slow, so that the mother cannot give enough milk to her baby. The cause of insufficient and slow breastfeeding is due to the presence of the hormone prolactin and the lactation process also depends on oxytocin. Massage rolling (back) is a relaxation therapy that aims to stimulate the central nervous system so that it can increase milk production, especially for post-partum mothers and can provide comfort and relaxation to the mother after childbirth. The rolling massage action (back) can affect the hormone prolactin, which acts as a stimulus for milk production in the mother during breastfeeding. There is also the aim of the results of this study that therapy or rolling massage (back) massage in post partum mothers can increase milk production. This research uses a quantitative approach, the method used in this research is quasi experimental. The type of design in this study was in the form of a non equivalent design (pretest and posttest). The sampling technique used was accidental sampling. The population in this study were post partum mothers at the Pratama Deliana Clinic Pekanbaru who experienced unsanitary breastfeeding. The results showed that the rolling massage method (back) was effective for increasing milk production in postpartum mothers with a p-value of 0.001 (<0.05). It is hoped that the need for socialization about rolling massage to mothers since pregnancy, both in the class of pregnant women or during pregnancy visit counseling. Socialization can also be in the form of leaflets or banners about rolling massage.